The Relationship between Adjustment Disorder and Emotional Regulation among Sample of adults in Tabuk - Algarni, Wejdan Abdulrhman; Alhomidi, Ahmed Ali (Journal of Educational and Psychological Sciences, 2023)
Objective of the study: To identify the extent to which adjustment disorder is related to emotional regulation in a sample of Saudis in Tabuk. Methods: Correlative descriptive curriculum has been used. Sample: The study community consists of the number of men and women patients aged 18 to 63 who reviewed the Irida and Mental Health Hospital in Tabuk and were diagnosed with coping disorder, depression, and anxiety from the period (2022- 2023), the number of whom (36) were selected in the manner available. Study tools: The study relied on a ADNM- 20 scale (Maercker et al., 2010) Translation of the researcher (Nihad, 2022), and a measure of emotional regulation (2007 preparation, Kraaij & Garnefski), translation of the researcher Mohammed Afana (2022). Results: The results resulted in negative emotional regulation strategies in a sample of Saudi patients in Tabuk having a positive and statistically significant relationship with Adjustment disorder, where the coefficient was valued (r = 0.688), which is a statistically positive value, and the positive emotional regulation strategies of a sample of Saudi patients in Tabuk are associated with a negative relationship and statistically altered with Adjustment disorder, where the binding coefficient (r =- 0.292), which is a negative value and statistically altered. The existence of a predictive force indicating a statistically D effect of emotional regulation strategies, both positive and negative and indicative (Sig F = 0.000) as indicators of coping disorder in a sample of Saudi patients in Tabuk.